The impact of drug-eluting bead (vs. conventional) transarterial chemoembolization on hepatic fibrosis in treating intermediate or advanced hepatocellular carcinoma - Hao Li; Chao Liang; Donglin Kuang; Guohao Huang; Mengfan Zhang; Pengfei Chen; Qingzhu Zheng; Wenze Xu; Jianzhuang Ren; Xinwei Han; Xuhua Duan (Cancer Biology & Therapy, 2023)
Objective Limited studies have reported the impact of drug-eluting bead transarterial chemoembolization (DEB-TACE) on hepatic fibrosis in hepatocellular carcinoma (HCC). This study evaluated multiple hepatic fibrosis indicators, aiming to comprehensively compare the influence of DEB-TACE and conventional transarterial chemoembolization (cTACE) on hepatic fibrosis in treating HCC patients. Methods Intermediate/advanced HCC patients (N = 121) were divided into the DEB-TACE group (n = 62) and the cTACE group (n = 59) based on their chosen treatment. Serum hyaluronic acid (HA), pro-collagen type-III (PC-III), collagen type-IV (IV-C), and laminin (LN) were detected; aminotransferase to platelet ratio index (APRI) and fibrosis index based on the four factors (FIB-4) were calculated; liver stiffness measurement (LSM) was assessed by real-time shear wave elastography. Results HA, PC-III, IV-C, and LN at 1 month after the second TACE and at 12 months after the first TACE were all decreased in DEB-TACE group compared with cTACE group (all P < .050). Then, APRI, FIB-4, and LSM were further assessed, which also showed a decreasing trend at aforementioned timepoints in DEB-TACE group compared with cTACE group (all P < .050). Additionally, the multivariate logistic regression analysis revealed that DEB-TACE (vs. cTACE) was independently associated with reduced occurrence of severe hepatic fibrosis at 12 months (OR = 0.215, 95%CI: 0.058–0.802, P = .022). Concerning the liver function indexes, alanine aminotransferase, aspartate aminotransferase, and total bilirubin after treatment were not different between the two groups (all P > .050). Conclusion DEB-TACE displays attenuated hepatic fibrosis progression and noninferior tolerance compared to cTACE in treating intermediate- or advanced-stage HCC patients.